2009
DOI: 10.1128/jvi.01476-09
|View full text |Cite|
|
Sign up to set email alerts
|

Apolipoprotein E but Not B Is Required for the Formation of Infectious Hepatitis C Virus Particles

Abstract: Our previous studies have found that hepatitis C virus (HCV) particles are enriched in apolipoprotein E (apoE) and that apoE is required for HCV infectivity and production. Studies by others, however, suggested that both microsomal transfer protein (MTP) and apoB are important for HCV production. To define the roles of apoB and apoE in the HCV life cycle, we developed a single-cycle HCV growth assay to determine the correlation of HCV assembly with apoB and apoE expression, as well as the influence of MTP inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
155
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(168 citation statements)
references
References 39 publications
(78 reference statements)
9
155
2
2
Order By: Relevance
“…The association appears to occur during assembly, because HCV formation and secretion depend on components of the very low density lipoprotein (VLDL) assembly and secretion pathways, including apolipoprotein E (apoE) and microsomal triglyceride transfer protein (19 -23). Whether apolipoprotein B (apoB) is also required for HCV assembly is discussed controversially (19,21,22,24). ApoB-containing lipo-viro-particles have been identified in patients (16).…”
Section: Flagmentioning
confidence: 99%
“…The association appears to occur during assembly, because HCV formation and secretion depend on components of the very low density lipoprotein (VLDL) assembly and secretion pathways, including apolipoprotein E (apoE) and microsomal triglyceride transfer protein (19 -23). Whether apolipoprotein B (apoB) is also required for HCV assembly is discussed controversially (19,21,22,24). ApoB-containing lipo-viro-particles have been identified in patients (16).…”
Section: Flagmentioning
confidence: 99%
“…It seems that HCV can hijack this function for its own assembly as it circulates in patient serum in association with lipoproteins [22,23]. Moreover, host factors crucial for production of VLDL like apolipoprotein E, apolipoprotein B and microsomal triglyceride transfer protein have been found to be important for production and release of infectious HCV particles [24][25][26][27][28][29]. The association of HCV with lipoproteins influences cell entry with the involvement of several lipoprotein (LDL receptor) [30,31] and lipid receptors (Scavenger receptor class B type I, SR-BI; Niemann-Pick C1-like 1 cholesterol uptake receptor, NPC1L1) [32,33].…”
Section: Hcv In the Infected Patientmentioning
confidence: 99%
“…Anti-E1/E2 Abs [9,11,62,148], patient sera [9], soluble E2 [46], lectins [150,151], anti-ApoE antibodies [29], apoE peptides [149] Abs, Erlotinib, Lapatinib, Gefitinib [141] EGF, TGF-α [141] HDL [138] ApoCI [139] BLTs [138,140] Abs, Dasatinib [141] Arbidol [144] Abs [109,137], ITX 5061 [134], natural ligands [135,136] Abs, soluble CD81 [9,11] Abs [142] Cldn1 peptide [143] Heparin, GAG nzymatic digestion [69,132] Abs, natural ligands, soluble LDL receptor [30,133] GAGs LDLR CD81 SR-BI Cldn1 Ocln…”
Section: Epha2mentioning
confidence: 99%
See 1 more Smart Citation
“…HCV production was reduced also by blocking VLDL assembly through knocking‐down or inhibition of MTP 45, 46. However, these observations were not always confirmed 47, 48, probably because of differences in VLDL synthesis capacity between different cell culture systems. It has been demonstrated that apoE interaction with HCV NS5A is crucial for the viral assembly process 49.…”
Section: Hcv Interaction With Lipid and Lipoprotein Metabolismmentioning
confidence: 97%